The effect of the application direction of the kinesiology tape on the strength of fatigued quadriceps muscles in athletes - Choi, I.-R.; Lee, J.-H. (Research in Sports Medicine, 2019)
This study aimed to determine the effects of application direction of the kinesiology tape on the strength of fatigued quadriceps muscles, and included 15 athletes (mean: age, 19.53 ± 2.42 years; height, 176.93 ± 6.9 cm; weight, 72.87 ± 13.02 kg). The kinesiology tape was randomly applied to the quadriceps from origin to insertion (n = 7) or from insertion to origin (n = 8) after inducing quadriceps muscle fatigue. After 1 week, the kinesiology tape was applied in the opposite direction (insertion to origin [n = 7] or origin to insertion [n = 8]) after inducing quadriceps muscle fatigue. The peak torque of the fatigued quadriceps muscles was measured before and after tape application. Increased peak torque values were observed irrespective of the direction of taping. No significant differences were noted in the peak torque of the fatigued quadriceps muscles with respect to application direction. Kinesiology tape application may improve the strength of fatigued quadriceps muscles regardless of application direction.